Behaviour Management with Young Children : crucial first steps with children 3-7 years - Rogers, Bill, 1947-; McPherson, Elizabeth (Teacher) (Los Angeles : SAGE, 2014)
Written by experts, this is an essential book for all early years students, infant teachers, support staff and school leaders. It explores behaviour management in the crucial early years of schooling in an accessible and practical way.
Previous edition: 2008.
Includes bibliographical references and index.
Keywords: Classroom management; Behavior modification; Elementary school teaching; Education